2014
DOI: 10.1089/ast.2013.0989
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Planetary Protection Measures on the Mars Science Laboratory

Abstract: The Mars Science Laboratory (MSL), comprising a cruise stage; an aeroshell; an entry, descent, and landing system; and the radioisotope thermoelectric generator-powered Curiosity rover, made history with its unprecedented sky crane landing on Mars on August 6, 2012. The mission's primary science objective has been to explore the area surrounding Gale Crater and assess its habitability for past life. Because microbial contamination could profoundly impact the integrity of the mission and compliance with interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 5 publications
0
39
0
Order By: Relevance
“…Hence, these systems were operating at cleanliness levels that far exceeded the requirements. Furthermore, the surfaces of the PLF were even cleaner and were shown to harbor a mere 4.65 spores/m 2 , which was even cleaner than the average 22 spores/m 2 reported on the MSL flight system hardware (Benardini et al, 2014). Sample blanks exhibited no colony counts.…”
Section: Standard Nsamentioning
confidence: 81%
“…Hence, these systems were operating at cleanliness levels that far exceeded the requirements. Furthermore, the surfaces of the PLF were even cleaner and were shown to harbor a mere 4.65 spores/m 2 , which was even cleaner than the average 22 spores/m 2 reported on the MSL flight system hardware (Benardini et al, 2014). Sample blanks exhibited no colony counts.…”
Section: Standard Nsamentioning
confidence: 81%
“…The amount of ATP in units of mmole/sample was then established by multiplying the calculated ATP concentration by the total sample volume. Individual ATP samples were then grouped into broad spacecraft “zones.” Zones were based on the broader spacecraft subsystems representing several larger flight system and launch vehicle components, such as the backshell, descent stage, heatshield, and rover (Benardini et al 2014). Finally, averages for bioburden densities and ATP mmole/zones were calculated for the specified spacecraft zones.…”
Section: Methodsmentioning
confidence: 99%
“…Samples were collected and processed by the Jet Propulsion Laboratory ( JPL) MSL Planetary Protection Implementation Team (Benardini et al, 2014). Cotton swabs and polyester wipes were used to collect samples (*25 cm 2 and 1 m 2 , respectively) from exterior surfaces of MSL.…”
Section: Sample Collectionmentioning
confidence: 99%
“…Over the last decade, a number of studies have reported on the microorganisms that are detectable in spacecraft assembly facilities during prelaunch preparations despite the precautions that were taken to reduce the microbial load (La Duc et al, 2004, 2007bKempf et al, 2005;Benardini et al, 2014). Previous studies testing survival of Earth microorganisms in simulated martian conditions have focused on spore-forming microorganisms, particularly bacteria of the Bacillus genus, since spores are hardy forms of terrestrial life that can survive Mars-like conditions (Horneck, 1993;Nicholson et al, 2000;Riesenman and Nicholson, 2000;Schuerger et al, 2003;Link et al, 2004;Newcombe et al, 2005;Tauscher et al, 2006;Zenoff et al, 2006;Fajardo-Cavazos et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation